2022
DOI: 10.1155/2022/3962011
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Sex Education and Its Effects on Adolescent Sexual Behavior in Nigeria

Abstract: Sexual behavior during adolescence fundamentally steers the future life of both girls and boys, and it should be guided with appropriate education, especially as it also represents a key factor to be considered in attainment of sustainable developmental goals. The study assessed the effect of exposure to sex education on adolescents’ sexual behavior. The primary and cross-sectional survey data used for this study were analyzed using basic descriptive statistics and binary logistic regression analytical techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
10
1
Order By: Relevance
“…This is because as adolescents get older, they always notice various changes in their bodies, which usually leads them to source information. The level of knowledge obtained in this study is higher than the 90.8% reported by Osadolor et al (2022) 12 . A higher percentage (97.3%) of female students than male students (94.2%) had heard about sex education (Table 3).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…This is because as adolescents get older, they always notice various changes in their bodies, which usually leads them to source information. The level of knowledge obtained in this study is higher than the 90.8% reported by Osadolor et al (2022) 12 . A higher percentage (97.3%) of female students than male students (94.2%) had heard about sex education (Table 3).…”
Section: Discussioncontrasting
confidence: 80%
“…In contrast, some studies on sex education have suggested that exposure to formal sex education appears to have no consistent effect on the subsequent probability that a teenager will begin to have intercourse 11 . Osadolor et al (2022) reported that most students (54.6%) received initial sex education from schools, while the least (4.9%) was from books and magazines, and recommended that streamlining sex education needs by age and sex characteristics could enhance its effectiveness since the needs of adolescents could vary by demographics 12 . Maimunah (2019) reported that to date, the concept of sex education is still considered taboo in the community and therefore rarely receives concern at both home and school 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The need to prevent and control the burden of STOIs in Nigeria is urgent [18]. However, with the limited socio-economic resources and the current fragility of the health workforce and health systems in Nigeria, the most sustainable approach is through public health education because it is effective, relatively cheaper, and easier than other public health intervention strategies [18,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This decontextualised exposure to sexual behaviour in adolescence has negative repercussions that can affect their sexual relationships into adulthood, as it can lead to an insensitive approach towards women, thus reinforcing social norms that sustain violence and sexual abuse [14,15]. A lack of understanding regarding sexual needs and sexual health negatively influences adolescents' future sexual behaviour [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have analysed adolescent sex education from the parents' perspective [29], the effects of sex education on adolescent sexual behaviour [16] or the relationship between sex education and the reduction in unintended pregnancies among adolescents [30], but little is known about adolescents' experiences of the sex education they have received. Understanding adolescents' perspectives on sex education received in Spanish schools allows us to identify their needs and make improvements.…”
Section: Introductionmentioning
confidence: 99%